2018
DOI: 10.21608/jpp.2018.35235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Some Agronomic Traits in Two Bread Wheat Crosses under Heat Stress Conditions.

Abstract: The present investigation aimed to determine genetic parameters and type of gene action controlling some agronomic traits of the two bread wheat crosses, Shandawel 1 × Gemmeiza 11 and Misr 1 × Giza 168 under normal 20 th Nov. and heat stress 20 th Dec. conditions, using six populations model (P 1 , P 2 , F 1 , F 2 , B C1 and B C2). Scaling test indicated the presence of non-allelic interactions for all studied traits except number of spikes/plant in cross 2 under normal conditions, number of grains/spike in cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The significance of additive (a) and dominance (d) components indicated that, both additive and dominance gene effects were important in the inheritance of these traits and selecting desirable traits may be practiced in the early generations but it would be effective in the late ones. Similar trend of results was obtained by Ashrei et al, (2013), El-Refaey andAbd El-Razek (2013), Abo Mostafa et al, (2014) and Abd El-Hamid and Ghareeb (2018).…”
Section: Discussionsupporting
confidence: 90%
“…The significance of additive (a) and dominance (d) components indicated that, both additive and dominance gene effects were important in the inheritance of these traits and selecting desirable traits may be practiced in the early generations but it would be effective in the late ones. Similar trend of results was obtained by Ashrei et al, (2013), El-Refaey andAbd El-Razek (2013), Abo Mostafa et al, (2014) and Abd El-Hamid and Ghareeb (2018).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the advancement of any plant breeding program is reliant upon the presence of genetic variability. Whereas, the efficiency of selection and expression of heterosis likewise depend on the magnitude of genetic variability in the plant population (Singh & Narayanan, 1993;Singh & Chaudhary, 1999;Farshadfar et al, 2001Farshadfar et al, , 2008aAmin, 2013;Abd El-Rady, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This condition causes great losses of yield due to high temperature during grain filling period. (Hamam, 2014;Raza et al, 2018;Abd El-Rady, 2018;Abdallah et al, 2019 andKoubisy 2019), had confirmed the damaging effect of heat on wheat.…”
Section: Introductionmentioning
confidence: 91%